2019
DOI: 10.4103/ajir.ajir_3_19
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Interventional Radiology among Clinical Years’ Medical Students and Medical Interns at University of Hail

Abstract: Context: One of the most important challenges facing the evolution of modern interventional radiology is its lack of awareness among medical students. Aims: This study aimed to determine the knowledge, perception, and views of the University of Hail clinical year medical students and medical interns regarding various interventional radiology topics. Settings and Design: A cross-sectional study on 244 clinical years' medical students and 87 medical interns from the University of Hail. Materials and Methods: A v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…This finding is in concordance with European, [6,11] Canadian, [5] and local studies. [1,2] Commander et al compared one medial school that offered a radiology course to another that does not offer a radiology course. [8] Fifty-four percent and 38% of medical students from the former and latter medical schools would consider IR as a career, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in concordance with European, [6,11] Canadian, [5] and local studies. [1,2] Commander et al compared one medial school that offered a radiology course to another that does not offer a radiology course. [8] Fifty-four percent and 38% of medical students from the former and latter medical schools would consider IR as a career, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Only a handful of studies have been published regarding this subject. [1,2] The growth and overall longevity of any medical specialty are heavily reliant on the recruitment of medical graduates who hold interest in these respected fields. This rule also applies to IR, and without the interest and knowledge of medical graduates toward IR, it could lose many of its possessed interventions to other subspecialties.…”
Section: Introductionmentioning
confidence: 99%
“…Medical students have had limited exposure to the IR specialty during their education and there is no official IR education in the undergraduate curriculum, for example, a 313-student survey in Spain found that medical students had limited awareness of IR (de Gregorio et al, 2018). We found several publications on Saudi medical students, one of which was a big study from Riyadh, Hail and Jeddah, all of which revealed insufficient exposure or knowledge to interventional radiology (Albaqawi et al, 2019;Alnajjar et al, 2019;Abohimed et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] In addition, several studies have illustrated that a structured undergraduate IR curriculum improved medical students' knowledge and regard of the specialty. [9][10][11] In relation to Saudi medical students, we found four studies, one of them being a large study from Riyadh 12 and northwestern 13 and southwestern Saudi Arabia 14,15 that unanimously reported poor knowledge and exposure to IR. Thus, we aimed to conduct this survey among Saudi medical students of Jazan University to explore the extent of their knowledge about IR, their interests in IR as a future career, and their preferred methods of learning about IR.…”
Section: Introductionmentioning
confidence: 99%